Early OCT Angiography Changes of Macular Neovascularization in Patients with Exudative AMD Treated with Brolucizumab in a Real-World Setting - Anne Rübsam; Saskia Rau; Daniel Pilger; Oliver Zeitz; Antonia M. Joussen (Journal of Ophthalmology)
Background. To report on the short-term outcome of intravitreal brolucizumab in patients with neovascular age-related macular degeneration (nAMD). Methods. This is a prospective, interventional, monocentric study on 10 eyes of 10 patients with a treatment-naïve neovascular AMD. Patients were treated according to the HAWK and HARRIER trials. After loading with 3 monthly injections, eyes received an injection 12 weeks after the upload (q12w) or were adjusted to an 8 week interval (q8w), if disease activity was present 8 weeks after the upload. Main outcome measures were the change in central retinal thickness (CRT) assessed by spectral domain optical coherence tomography (SD-OCT), the change in macular neovascularization (MNV) size on optical coherence tomography angiography (OCTA), and the change in best corrected visual acuity (BCVA) 8 and 12 weeks after the upload. We further assessed clinical parameters that predict the treatment response at baseline based on the need of q8w or q12w injections after the upload. Results. CRT decreased significantly from 461.7 ± 82.9 μm to 343.6 ± 74.3 μm (p=0.004) 12 weeks after the upload. The MNV size decreased significantly from 0.85 ± 1.1 to 0.75 ± 1.2 mm2 (p=0.022). BCVA improved from 0.67 ± 0.4 to 0.55 ± 0.4logMAR but without statistical significance. MNV size in eyes on q12w was considerably smaller compared to that in eyes on q8w (0.54 ± 0.7 mm2 vs. 1.98 ± 2.4 mm2). The percentage of eyes without any persistent fluid was 70% (7/10 eyes). Conclusions. Brolucizumab appears to be a valuable tool for the management of patients with nAMD. Furthermore, MNV size at baseline might serve as an early predictor of treatment response.